The Values In Wayang Golek Entrepreneurship - Bahagia; Leni Muniroh2; Abdul Karim Halim; Rimun Wibowo; M. Azhar Al-Wahid (al-Afkar, Journal For Islamic Studies, 2022)
The main objective of this research is to find religious, social and cultural values based on wayang golek entrepreneurship. The research method used is a qualitative method. Meanwhile, the respondents were taken using purposive technique. Data collection is done by in-dept-interview, documentation, and observation. The results of the study indicate that there are moral values in the wayang golek business because to make wayang, one must understand the character of the wayang. While the puppet characters include wisdom, musharaka, and honesty. second, the preservation of wayang is carried out by providing training to elementary school students so that the younger generation understands wayang. In addition, the wayang market is held from Bogor, DKI. Jakarta, D.I. Yogyakarta, and Bali. Finally, making puppets must pay attention to the type of wood because the wood used will be related to the resistance of the puppets.